2021
DOI: 10.1080/17565529.2021.1937030
|View full text |Cite
|
Sign up to set email alerts
|

Extreme heat vulnerability assessment in tropical region: a case study in Malaysia

Abstract: In the past decade, the inevitable increase in temperature has caused Malaysia to experience more extreme heat events, and yet very little research has been dedicated in exploring the heat-related vulnerability of exposed population. In this study, the extreme heat vulnerability index (EHVI) has been evaluated to identify the most vulnerable districts to extreme heat events. We evaluated exposure, population sensitivity and adaptive capacity from sociodemographic and remote sensing data. We have applied multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…The spatial distribution of human populations in urban, sub-urban, and rural areas increases vulnerability to the health impacts of climate change (16,48,49,59,62,67,70,90,91,94,96,98,105,109,116,118,144,149,162,168,172,187,193,194). Urban and sub-urban areas have higher population densities (25,41,45,48,58,62,75,98,105,109,113,119,127,151,162,171,178,(196)(197)(198)(199)(200)(201) and larger population sizes (98,202,203...…”
Section: Urbanness and Remotenessmentioning
confidence: 99%
See 4 more Smart Citations
“…The spatial distribution of human populations in urban, sub-urban, and rural areas increases vulnerability to the health impacts of climate change (16,48,49,59,62,67,70,90,91,94,96,98,105,109,116,118,144,149,162,168,172,187,193,194). Urban and sub-urban areas have higher population densities (25,41,45,48,58,62,75,98,105,109,113,119,127,151,162,171,178,(196)(197)(198)(199)(200)(201) and larger population sizes (98,202,203...…”
Section: Urbanness and Remotenessmentioning
confidence: 99%
“…Studies consistently found access to health services and medical infrastructure are among the most influential indicators for sensitivity and adaptative capacity, especially for developing countries (69,183), and limited access to or lower quality of health services is associated higher vulnerability (87,89,117,151,198). People with pre-existing illness such as cardiovascular and respiratory disease (47,198), children (103,105,206), and the elderly (47,55,216) are particularly vulnerable due to additional medical needs and poor physical resistance to climate impact.…”
Section: Access To Health Care Servicesmentioning
confidence: 99%
See 3 more Smart Citations